The Repression of the HMGB1-TLR4-NF-κB Signaling Pathway by Safflower Yellow May Improve Spinal Cord Injury - Wang, Lu; Botchway, Benson O. A.; Liu, Xuehong (Frontiers in Neuroscience, 2021)
Spinal cord injury (SCI) often results in abnormal sensory and motor functions. Current interventions for SCI in the clinical setting are not effective partly due to the complexity concerning its pathophysiological mechanism. In the wake of SCI, considerable inflammatory cells assemble around the injured area that induces a series of inflammatory reactions and aggravates tissue lesions, thereby affecting the recovery of the damaged nerve tissue. Therefore, the inhibition of inflammatory responses can improve the repair of the injured spinal cord tissue. Safflower Yellow (SY) is the main active ingredient of Carthamus tinctorius. SY has anti-inflammatory effect, as it can inhibit IκBα phosphorylation to impede the NF-κB signaling pathway and p53 nuclear translocation. Besides, SY can limit the release of pro-inflammatory factors, which in turn may alleviate secondary SCI and prevent further complications. In this report, we analyze the pathophysiological mechanism of SCI, the role of inflammatory responses, and how SY interferes with the HMGB1-TLR-4-NF-κB signaling pathway to attenuate inflammatory responses in SCI.